Flexural strengthening of RC beams by using a near surface mounted T-section profiles - Chołostiakow, Szymon; Kotynia, Renata (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents test results of an experimental program of four full-scale RC beams, strengthened in flexure with T-section carbon fiber reinforced polymer (CFRP) profiles and two reference beams subjected to a six point bending. The novel shape of CFRP profile combines both the near surface mounted (NSM) and externally bonded (EB) strengthening systems. The application of the CFRP profiles consisted of gluing both the web and the flange of the profile to the concrete surface. RC beams made of the same concrete class were differed by the internal steel reinforcement ratio and in a number of applied profiles. Efficiency of this new strengthening product was determined by comparison of the strengthened and non-strengthened RC beams. An increase of the CFRP-concrete bond area and high stiffness of the T-section profiles significantly improved the strengthening ratio (up to 130% of the reference beam) and reduced the maximum mid-span deflection (ranged of 70-80%) of the non–strengthened beams. The CFRP strain utilisation equal to 67% of the tensile strain corresponded to the maximum CFRP strains equal to 0,73%. The promising test results exhibit this system as a very attractive proposal of new strengthening technique used for field applications of the existing structures.